Nursing throughout war times: political propaganda and professional valorization (1942-1945) - Thais da Silva Kneodler; Graciele Oroski Paes; Fernando Rocha Porto; Pedro Ruiz Barbosa Nassar; Alexandre Barbosa de Oliveira
ABSTRACT Objective: to discuss the symbolic effects of the publication on written press of institutional rites related to the courses promoted by the Brazilian Federal District's Schools of Nursing during the Second World War. Method: exploratory and documentary study, whose sources were treated by historical method. Results: one noticed, in the news reports analyzed, that the Brazilian Estado Novo has used nurses images to divulge within the society the woman's acting altruistic model in service to the country, through the systematic diffusion by the press of her honorable acting during the war, what assured the amplification of the visibility and acknowledgment of the Nursing profession in that context. Conclusion: the diffusion by press of emergency nurses graduations magnified their apparition in public spaces, occasion on which the institutional rite was strategically used to transmit to the society the urgency of the new profession, in order to support the political causes in vigor in the country.